Hormonal and metabolite responses to glucose and maltodextrin ingestion with or without the addition of guar gum. - MacLaren, D; Reilly, T; Campbell, I; Frayn, K (1994)
The purpose of this study was to examine the effects of ingesting water (P), a glucose solution (GL), a maltodextrin solution (Md), a glucose solution with 8% guar gum (GL+G), and a maltodextrin solution with 8% guar gum (Md+G), on the hormonal and metabolite responses during cycling, and on subsequent time to exhaustion. Five male subjects undertook five 90 min rides on a bicycle ergometer at an exercise intensity corresponding to 65% VO2max after having ingested 1 g.kg-1 body weight of the test product in 400 ml of water immediately before the exercise. Blood samples were taken during the trials for analyses of adrenaline, noradrenaline, insulin, glucagon, glucose, lactate and non-esterified fatty acids (NEFA). Respiratory measures were also undertaken during the trials for the determination of oxygen consumption (VO2) and respiratory exchange ratio (RER), from which the carbohydrate oxidation rates were calculated. Rates of perceived exertion (RPE) were also assessed. Ten minutes after the 90 min ride, subjects exercised to volitional exhaustion at an exercise intensity of 75% VO2max. ANOVA revealed that there were significant differences between the treatments for adrenaline (p < 0.01), insulin (p < 0.05), glucose (p < 0.01), lactate (p < 0.01), NEFA (p < 0.01), RER (p < 0.001) and carbohydrate oxidation rate (p < 0.01).(ABSTRACT TRUNCATED AT 250 WORDS)